The Effect of The Mind Map Method on The Students’ Memory in Thematic Learning - Harits, Dea Amelia; Mizaniya, Mizaniya (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2021)
Mind mapping is a method that can optimize students' memory, because it uses images, lines, colors, and symbols that can stimulate the child's double senses, in addition mind mapping can also maximize their brain abilities. The purpose of this study was to find out the influence of mind map method on the memory of learners in thematic learning in class IV MI Ma'arif NU 02 Tamansari. This research is a type of pre-experimental research conducted with the design of one group pretest posttest. The population in this study was all students in grade IV MI Ma'arif NU 02 Tamansari. Data collection techniques used in the form of observation, interviews, tests, and documentation. Test instruments use a type of short fill test that has been through the analysis of validity and reliability. Data analysis techniques use prerequisite test analysis in the form of normality and homogeneity test, and hypothesis test using statistical test paired sample t test. The results showed that the mind map method affects the memory of learners. This was demonstrated by Sig. (2-tailed) t test result with a significance of 0.000 less than 0.05. So, Ha was accepted and H0 was rejected, meaning that the mind map method affects the memory of the learners.